Neutralization and Violence in Gaza: How Jewish College Students in the United States and Israel Justify and Contest Military Engagement - Amy Adamczyk (Socius)
The October 7, 2023, Hamas attack on Israel and the subsequent military response sparked global controversy, deeply affecting young American and Israeli Jews. Drawing on 20 interviews with Jewish college students from both countries, this study explores how they interpret Israel’s actions through the lens of neutralization theory. Although most participants used traditional neutralization techniques to justify or rationalize Israel’s military engagement, a significant minority articulated counternarratives, challenging dominant frames of justification. Denial of victim was the most common technique, though its application varied by country; American students were not only more likely to use this justification but also more inclined to acknowledge the suffering of Gazan residents. Israeli students, by contrast, were more likely to appeal to higher loyalties, emphasizing national duty and security. These findings extend the application of neutralization theory beyond its typical focus on deviant behavior to illuminate how individuals make sense of morally charged situations involving state violence. By demonstrating how young people navigate competing values, reconcile personal and national identities, and construct narratives around military operations, this study provides new insights into the moral reasoning processes shaped by national context and lived experience.